USED PATTERN OF METALS AND MINERALS IN ASHTANG HRIDAYA: THE BIRDS EYE VIEW - Dighe, *Dattatray Pandurang; Kumar Ratha, Kshirod; Panda, Purnendu; P S, Aswani; Rao, M. M. (International Journal of Ayurveda and Pharma Research, 2018)
Human evolution and progress has count mainly on the discovery of metals. Primitive man used metals first time for making apparatuses and weaponries; as the information advances metals played a significant role in development of agriculture, transport arts, crafts and health care. Ayurveda have faith in the principle of YatPinde Tat Bramhande and therefore all these naturally occurring metals and minerals have major role in restoration of human health and treatment of any kind of illness. Classical treatise Ashtanga Hridaya is a very popular book among the physicians among south India. In this classic, eight types of Dhatu (metals), varieties of Ratna-Uparatna (precious stones and minerals) are mentioned for different purposes. Here an attempt is made to collect all these information of metals and minerals in a collective form to analyse their used pattern in therapeutic, Diagnostic (Nidana Panchaka), Pharmaceutical Benefits, Dincharya/ Pathya- Apathya, Panchakarma and Surgical/Para Surgical Procedure. All these metals and minerals are used in different formulations like Sneha (Oil &Ghee), Sandhana (Fermentation), Churna (powder), Vati (tablet), Lepa (Caoting powder) & Anjana (Collyrium). Human body is composed of almost every natural element found in nature and our civilization is completely reliant on metals and the science of metallurgy is now one of the most widely documented and researched material science.